2012
DOI: 10.4184/asj.2012.6.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Pedicle Screw Fixation Combined with Laminoplasty for Cervical Spondylotic Myelopathy with Instability

Abstract: Study DesignA retrospective study.PurposeTo evaluate the surgical results of cervical pedicle screw (CPS) fixation combined with laminoplasty for treating cervical spondylotic myelopathy (CSM) with instability.Overview of LiteratureCervical fixation and spinal cord decompression are required for CSM patients with instability. However, only a few studies have reported on CPS fixation combined with posterior decompression for unstable CSM patients.MethodsThirteen patients that underwent CPS fixation combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…However, they did not describe the preservation of the muscle attachment at the C2 level in the technique. Conversely, Cho [37] and Sakaura et al [40] preserved the C2 muscle attachment in their technique, and this resulted in lesser loss of cervical lordosis than that reported by Uehara et al [34]. Interestingly, Su et al [36] reported lesser loss of cervical lordosis after performing C3-C6 laminoplasty without preserving the C2 muscle attachment.…”
Section: Radiological Outcomementioning
confidence: 75%
See 4 more Smart Citations
“…However, they did not describe the preservation of the muscle attachment at the C2 level in the technique. Conversely, Cho [37] and Sakaura et al [40] preserved the C2 muscle attachment in their technique, and this resulted in lesser loss of cervical lordosis than that reported by Uehara et al [34]. Interestingly, Su et al [36] reported lesser loss of cervical lordosis after performing C3-C6 laminoplasty without preserving the C2 muscle attachment.…”
Section: Radiological Outcomementioning
confidence: 75%
“…Most of these studies used the JOA score as a parameter of clinical outcome. They reported that laminoplasty provided significant enhancement of the JOA score in the short-term, mid-term, and long-term follow-up [34][35][36][37][38][39]. However, Sakaura et al [40] reported that the average JOA score was at its highest point in 12 months of follow-up and decreased slightly to 14.9 in the final follow-up.…”
Section: Clinical Outcomementioning
confidence: 96%
See 3 more Smart Citations